Wasiat sebagai Instrumen Perubahan Hukum Keluarga di Indonesia - Sidik Tono (Universitas Islam Indonesia, 2005)
The last will (wasiat) of deceased person is a part of law regulation that conducted by society. This regulation generally has been introduced by Islamic law and other system of law in Indonesia. The will according to fiqh is only one side's action and it becomes charity agreement, meanwhile according to Alquran and prophet tradition, the position of the will consitutes integrative position in term of Islamic inheritance law. For that reason, it needs reinterpreting so that the will will becomes as an instrument to change family law in Indonesia.